Misogyny as hate crime - Zempi, Irene, 1984-; Smith, Jo, 1978- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Misogyny as Hate Crime explores the background, nature and consequences of misogyny as well as the legal framework and UK policy responses associated with misogyny as a form of hate crime. Taking an intersectional approach, the book looks at how experiences of misogyny may intersect with other forms of hate crime such as disablism, Islamophobia, anti-Semitism, and transphobia. From the sexist and derogatory comments about women by former US President Donald Trump, to legislative changes in Chile and Peru making street harassment illegal, misogyny presents a challenge to scholars, practitioners, policy makers, and women globally. The increasing importance of the internet has seen misogyny move into these digital spaces but has also provided a platform for movements such as #MeToo and #TimesUp, highlighting the scale of sexual harassment and abuse. In 2016, Nottinghamshire Police in partnership with Nottingham Women's Centre became the first force in England and Wales to record misogyny as a hate crime. Since then other police forces have introduced similar schemes to tackle misogyny. More recently, the Law Commission of England and Wales has undertaken a review of the legislation on hate crime and in their consultation paper of proposals for reform have suggested 'adding sex or gender to the protected characteristics'. Against this background, the book speaks both to the proposed reforms of the hate crime legislation around misogyny, and the broader issues around experiences of and legal responses to misogyny. It showcases the work of leading scholars in this area alongside that of activists and practitioners, whose work has been invaluable in opening up public discussion on misogynistic hate crime and encouraging wider social change. In recognising the intersections of different forms of prejudice, the book provides an innovative contribution to these 'hate debates', highlighting the complexities of creating separate strands of hate crime. Providing a comprehensive understanding of the debates around inclusion of misogyny as a form of hate crime, this ground-breaking book will be of great interest to students, scholars and activists interested in gender, hate crime, feminism, criminology, law, policing and sociology"--
Theorising misogyny, gender and 'hate crime' -- A feminist theoretical exploration of misogyny and hate crime / Marian Duggan and Hannah Mason-Bish -- Extending the concept, or extending the characteristics? Misogyny or gender? / Kim McGuire -- Online and offline spaces -- Gender as a protected characteristic: a legal perspective / Chara Bakalis -- Online misogyny as a hate crime: #TimesUp / Kim Barker and Olga Jurasz -- From sexism to misogyny: can online echo chambers stay quarantined? / Alexandra Krendel -- Identities and lived experiences -- Adolescent girls' experiences of street harassment: emotions, comments, impact, actions and the law / Rachel Harding, Lucy Betts, David Wright, Sheine Peart and Catarina Sjolin -- Misogyny, hate crimes and gendered Islamophobia: Muslim women's experiences and responses / Amina Easat-Daas -- The intersection of antisemitism and misogyny / Lesley Klaff -- An exposition of sexual violence as a method of disablist hate crime / Jane Healy -- Trans identities, cisgenderism and hate crime / Michaela Rogers -- "Not the right kind of woman": transgender women's experiences of transphobic hate crime and trans-misogyny / Ben Colliver -- Practice and activism -- A call to feminist praxis: the story of Nottingham's misogyny hate crime policy / Zaimal Azad and Sophie Maskell -- Policing misogyny as a hate crime -- the Nottinghamshire police experience / Sue Fish -- Informing legal change: the language of misogyny hate crime, gender and enhancing protection through criminal law / Louise Mullany, Loretta Trickett and Victoria Howard -- Our streets now: demanding an end to public sexual harassment / Maya Tutto.
OCLC-licensed vendor bibliographic record.
Keywords: Misogyny; Misogyny -- Great Britain; Sexual harassment of women; Sexual harassment of women -- Great Britain; Hate crimes; Hate crimes -- Great Britain; LAW / Criminal Law / General; LAW / Gender & the Law; SOCIAL SCIENCE / Criminology